Cuidar a personas mayores que viven en residencias en tiempos de covid-19 - Armengou Fal-Conde, Montserrat; March Álvarez, Eva; Julià Juncadella, Roser; Maura Riera, Roser; Graell Tor, Montserrat; Forné Gonzalez, Susanna (HEALTH, AGING & END OF LIFE, 2023)
Sin resumen